Analysis on the Factors of Declining the Collection of Agricultural Zakat - Abdul Rahim, Ahmad Khilmy; Mohd Noor, Mohd Murshidi; Ahmad Razimi, Mohd Shahril; Abu Bakar, Azizi (Universidad del Zulia, 2020)
In Malaysia, the agricultural produce that is required to pay zakat is in the form of staple food (qut al-balad) that is filling on a state. This meaning is used by most zakat institutions in Malaysia namely Kedah (State Zakat Board), Selangor (Selangor Zakat Board), Malacca (Melaka Zakat Center), Pahang (Pahang Zakat Collection Center) and others. In the Malaysian context it is understood that the staple food of the people is rice (paddy). Therefore, zakat on crops is compulsory on rice when certain conditions are fulfilled. Kedah is considered as the "rice bowl"(Jelapang Padi) of Malaysia, accounting for about half of Malaysia's total production of rice. Base on the statement, Kedah should have a high collection of agricultural zakat. Recently, data shows that the collection of agricultural zakat among the farmers in Kedah is declining due to certain factors and issues. Using qualitative method, this article analyses the historical aspect, fatwas, legality and current implementation of agricultural zakat in Kedah. Further, using interview and documentation method, the study analyses the factors of declining the collection of agricultural zakat in Kedah